Revealing the Therapeutic Potential of Stem Cells in Burn Healing: A Deeper Understanding of the Therapeutic Mechanisms of Epidermal Stem Cells and Mesenchymal Stem Cells - Jianyu Lu; Wei Zhang; Yushu Zhu; Pengfei Luo; Xirui Tong; Sujie Xie; Luofeng Jiang; Xinya Guo; Jie Huang; Minyi Gu; Xinran Ding; Shuyuan Xian; et al. (Stem Cells International)
Conclusion: The present study obtained deep insight into the developing trends and research hotspots on burns associated with stem cells, which arouses growing concerns and implies increasing clinical implications. The mechanism and therapeutics of epidermal stem cells (ESCs) for burn wounds and the mechanism of mesenchymal stem cells (MSCs) and MSC-derived exosomes for burns wounds are two research hotspots in this field.